Maqashid al-Shariah dan Kearifan Lokal: Tinjauan al-Qur'an Tentang Pelestarian Kerukunan dan Toleransi Beragama - Ulumudin, Ihya’; Lubis, Ahmad Hafidz; Farid, Achmad (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
This research examines the synergy between Tafsir Maqashidi and local wisdom in Senduro Village, Senduro District, Lumajang Regency, in maintaining religious harmony and tolerance. The research object includes Qur'anic verses related to moderation and local wisdom, such as the tradition of gotong royong and deliberation, which support social harmony in the village. The research objective is to understand how Islamic values in maqashid al-shariah can be integrated with local wisdom to create a tolerant society. This research uses a qualitative method with a Maqashidi tafsir approach and content analysis of verses such as QS. Al-Baqarah [2]: 256 and QS. Al-Hujurat [49]: 13. The results show that Maqashidi tafsir reinforces the importance of moderation in maintaining harmony, and local wisdom in Senduro acts as a bridge in creating interfaith harmony. In conclusion, the integration between Maqashidi interpretation and local wisdom in Senduro Village is an effective strategy in maintaining social stability and interfaith tolerance